Contextualizing women's and men's trait preferences and choice options in the uptake of breeding products: a framework - Cavicchioli, M.; Cole, Steven M.; Teeken, B.; Ashby, Jacqueline A.; Polar, V.; Kramer, Berber; Yami, M.; Abdoulaye, T. (International Institute of Tropical Agriculture, 2023)
Women and men value chain actors in low-income countries assess and choose varieties, animal breeds, or strains according to a multitude of factors, such as local agroecological conditions, production and consumption habits, and seed availability and accessibility. Continuous changes in the ecological, economic, and political contexts shape women’s and men’s day-to-day social interactions as well as their livelihood options and can create new needs for specific breeding products. However, the uptake of new breeding products is also contingent on women’s and men’s range of choice options. The existence and extent of these choice options depend on one’s social and economic position and capacity to negotiate access and control over strategic resources.